Healthy Living: Are You at Risk for Drug Interactions? - Jennifer Hillan; Linda B. Bobroff (EDIS, 2010)
Revised! FCS8621, a 1-page handout by Jennifer Hillan and Linda B. Bobroff, provides a list of 9 questions to help people determine whether they are at risk of drug interactions. Published by the UF Department of Family Youth and Community Sciences, August 2010.